Development and Evaluation of the Acceptability of Soy-Based G-Max Coffee as an Iron-Rich Functional Beverage - Lailatus Sa'idah; Efina Amanda; Elita Endah Mawarni (Indonesian Health Issue, 2026)
ABSTRACTBackground: Anemia in adolescent girls remains a serious public health problem in Indonesia due to the high iron requirement during growth and menstruation. The habit of consuming coffee containing caffeine and tannins can inhibit iron absorption, so it is necessary to innovate alternative drinks that are safer, more nutritious, and have the potential to help prevent anemia. Purpose: This study aims to develop G-Max Coffee made from soybeans as an alternative drink for adolescent girls with anemia and to analyze the acceptability, nutritional content, iron, tannin, and caffeine levels in the best formulation. Methods: This study used an experimental design with a Completely Randomized Design (CRD) consisting of three formulations (F1, F2, and F3). Hedonic tests and hedonic quality were conducted on 30 untrained panelists. The best formulation was determined using the Bayes method, then analyzed for nutritional content, iron, tannin, and caffeine levels through laboratory tests. Data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test. Results: Formulation F1 (70% soy coffee : 30% palm sugar) was the best formulation with the highest level of panelist acceptance. Laboratory analysis showed energy content of 23.37 kcal, protein 2.09%, fat 0.69%, carbohydrate 2.20%, iron 0.70 mg/100 g, tannin 0.031 mg QE/100 g, and no caffeine. Conclusion: G-Max Coffee formulation F1 has the potential to be an alternative drink for young women with anemia because it has good acceptability, contains iron, is low in tannin, and is caffeine-free. Further research is recommended to conduct intervention trials to assess its effectiveness in increasing hemoglobin levels.